Implementasi Jaringan VPN (L2TP/Ipsec) Mikrotik Untuk Remote Access Sebagai Security Selama Work From Home - Bayu Gagat Rahino; Atang Susila (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
During the COVID-19 pandemic, PT XL Axiata implemented a work from home policy, which requires employees to be able to connect to the company's network and data using the internet or public networks. Wiretapping by people who do not become more likely when using a public network. Employees of PT XL Axiata tbk can connect to the company's network and data using public networks safely and easily using VPN as a security solution. A virtual private network (VPN) provides a secure remote connection for clients to exchange information with the corporate network. This research is related to L2TP/IPSec-VPN connecting corporate intranet. L2TP/IPSec-VPN networks are implemented with security protocols for key and exchange management, authentication, and integrity using virtual devices with the Vmware Workstation assistance program. Data packet testing and analysis is performed using PING and Wireshark tools to ensure packet data encryption during data exchange between different networks belonging to the same company. The methodology used in this research is to collect data through surveys and interviews, then analyze the current network and the need for network design support. in order to increase employee productivity and performance while working from home, as well as being able to compete with other businesses in an increasingly competitive market.